Implementation of Traveling Salesman Problem (TSP) based on Dijkstra's Algorithm in the Information System of Delivery Service - Syahputra, M. Firman Aji; Devita, Riri Nada; Siregar, Sherly Allsa; Kirana, Kartika Candra (JAVA Journal of Electrical and Electronics Engineering, 2016)
Traveling Salesman Problem (TSP) was defined as a task for finding of the shortest route. The finding  of  the  shortest  route influences a price of delivery service and profit of company.  Therefore, we proposed an implementation of Traveling Salesman Problem (TSP) based on Dijkstra’s Algorithm in a information systems of delivery services" for optimizing the finding of shortest route. This algorithm using distance which is extracted from Google Maps. There are 60 routes which are tested. The results show the accuracy of TSP based on Dijkstra’s algorithm is 100%. The results can be concluded that the implementation of Dijkstra’s algorithm is accurate for finding the shortest route.